2014
DOI: 10.1371/journal.pone.0100913
|View full text |Cite
|
Sign up to set email alerts
|

Weekly and Holiday-Related Patterns of Panic Attacks in Panic Disorder: A Population-Based Study

Abstract: BackgroundWhile chronobiological studies have reported seasonal variation in panic attacks (PA) episodes, information on the timing of PA by week-days may enable better understanding of the triggers of PA episodes and thereby provide pointers for suitable interventional approaches to minimize PA attacks. This study investigated weekly variation in potential PA admissions including associations with holidays using a population-based longitudinal, administrative claims-based dataset in an Asian population.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We also speculate that differences in behavioral choices during weekdays and weekend-days may have differential effects on anxiety, as one study showed that anxiety is more pronounced during the weekend 48 . Therefore, this study aimed to investigate the impact of housing quality and weekend/holiday sedentary behavior on the central nervous system, specifically on brain structure and anxiety (see Fig.…”
Section: Introductionmentioning
confidence: 92%
“…We also speculate that differences in behavioral choices during weekdays and weekend-days may have differential effects on anxiety, as one study showed that anxiety is more pronounced during the weekend 48 . Therefore, this study aimed to investigate the impact of housing quality and weekend/holiday sedentary behavior on the central nervous system, specifically on brain structure and anxiety (see Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Sleeping is another central behavior that follows a weekly pattern, typically with a lack of sleep during the workweek (“social jet lag”) and compensatory sleeping on days off [ 7 , 8 ]. Mood and level of aggression also follow various cycles; for instance, suicides are most frequent on Mondays and panic attacks are most frequent on days off from work [ 9 - 12 ].…”
Section: Introductionmentioning
confidence: 99%